Exploratory Analysis of Concordance Between Clinician-Collected and Self-Sampled Human Papillomavirus Tests in a Small Cohort of Average- and High-Risk Patients - Ashley Wong; Rebecca Morgis; Juliette Entenman; Sarah I. Ramirez; Amy L. Hays; Tonya S. Wright; Christina M. Scartozzi; Mack T. Ruffin; Jennifer L. Moss (Women's Health Reports)
Objectives: Cervical cancer screening rates have stagnated, but self-sampling modalities have the potential to increase uptake. This study compares the test characteristics of self-sampled high-risk human papillomavirus (hrHPV) tests with clinician-collected hrHPV tests in average-risk (i.e., undergoing routine screening) and high-risk patients (i.e., receiving follow-up after abnormal screening results). Methods: In this cross-sectional study, a relatively small cohort of average-risk (n = 35) and high-risk (n = 12) participants completed both clinician-collected and self-sampled hrHPV testing, along with a brief phone survey. We assessed hrHPV positivity, concordance, positive predictive value (PPV), negative predictive value (NPV), sensitivity, and specificity across both methods (for types 16, 18, or other hrHPV). We also explored the relationship between test concordance and sociodemographic/behavioral factors. Results: Among average-risk participants, hrHPV positivity was 6% for both test methods (i.e., hrHPV-positive cases: n = 2), resulting in reported concordance, PPV, NPV, sensitivity, and specificity of 100%. Among high-risk participants, hrHPV positivity was 100% for clinician-collected tests but only 67% for self-sampled tests, showing varied concordance and sensitivity. Concordance was not associated with sociodemographic or behavioral factors. Conclusions: Self-sampled hrHPV testing demonstrated high accuracy for average-risk patients in this exploratory study. However, its performance was less consistent in high-risk patients who had already received an abnormal screening result, which could be attributed to spontaneous viral clearance over time. The limited number of participants, particularly HPV-positive cases, suggests caution in interpreting these results. Further research with larger cohorts is necessary to validate these findings and to explore the integration of self-sampled hrHPV testing into routine clinical care, particularly for patients with a history of cervical abnormalities. Clinical Trial Registration: NCT04591977, NCT04585243.